A Comparative study of Islamic and Conventional Banks Risk Management Operating in QISMUT Countries - Kmaly, Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The clue of a good financial management for any bank or financial institution is risk management. The most important part of the process of risk management is to identify and determine the source of risk. This study is carried out in order to identify and analyze the factors that influence credit risk, liquidity risk and capital risk of both Islamic and conventional banks in QISMUT countries (Qatar, Indonesia, Saudi Arabia, Malaysia, UAE and Turkey) during the period from 2011 to 2015 taking in to consideration answering research question if determinants of risk in Islamic banking sector are the same as conventional banking sector or not. Concerning credit risk log of bank size is only common factor that significantly affects both Islamic and conventional banks. Bank fund management is the only factor that shows significant impact to both Islamic and conventional banks. Deposits structure is considered to be the only significant factor that influence capital adequacy of both Islamic and conventional banks. From the investigated factors for each risk there is only factor which has significant impact on Islamic and conventional banks. This indicates that there is a big difference in the factors that influence risk in Islamic and conventional banks and this may be due to the factors mentioned in chapter 1 that differentiate Islamic banking from conventional banking. Keywords: Islamic banks, Conventional banks, Credit risk, Liquidity risk, Capital risk.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Banks and Banking-Islamic Banking-Conventional Banking; Islamic banks; Conventional banks; Liquidity risk; Capital risk; Credit risk